The cost of debt capital revisited - Rainer Baule (Business Research, 2019)
We propose a method to estimate the cost of debt in a continuous-time framework with an infinite time horizon. The approach builds on the class of well-known earnings before interest and taxes (EBIT)-based models. It extends other approaches based on option-pricing theory with a finite one-period horizon. The model is capable of splitting the observed yield spread of a corporate bond into the risk premium, which adds to the expected return of bondholders, and the default premium, which accounts for expected losses. The model can easily be calibrated for non-public firms, since most of its input parameters are readily observable, while the output, the model-implied cost of debt, proves to be very insensitive with respect to the remaining non-observable parameters, the EBIT growth rate, and the bankruptcy costs of the firm. We demonstrate the applicability of the cost of debt to calculate an approximate weighted average cost of capital for the purpose of firm and project valuation, and its usage and limitations.
Keywords: 650; Cost of capital; Cost of debt; EBIT-based model; WACC; Yield spread